Sektor Industri pada Pembangunan Makro Ekonomi di Kota Surabaya - Muhammad Ilham Januarta; Muhammad Yasin (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Indonesia's rapid population growth requires the economy to grow at least 2.2% every year to keep per capita output stable. This results in high labor force growth that is difficult to overcome. Labor absorption must be in line with economic growth to prevent disparities. The processing industry sector plays a major role in the strategy for employment absorption and economic growth. This industry is also considered a leading sector in the economy, with a favorable exchange rate and creating higher added value. In Surabaya, economic growth and per capita income are higher than other areas in East Java. This city has great potential to develop promising sectors and encourage economic growth. Regional economic conditions, including GRDP, taxes, inflation, investment and other economic services, can reflect the success of a region.